Pengaruh Asimetri Informasi, Regulasi Perbankan, dan Ukuran Perusahaan pada Manajemen Laba dengan Model Akrual Khusus Perbankan (Studi Empiris pada Industri Perbankan di Indonesia yang Terdaftar di BEJ) - Rahmawati Rahmawati; Zaki Baridwan (Jurnal Akuntansi dan Bisnis, 2006)
The purposes of this research are: (1) to test the influence of information asymmetry on earnings management, (2) to test the influence banking regulation on earnings management, (3) the influence of firm size on earnings management. This research data are collected from ICMD (Indonesian Capital Market Directory) and/or annual report company which are provided by the Capital Market Reference Center (PRPM) of Jakarta Stock Exchange (JSX) and also financial statement of public banking companies published by Indonesia Banking Directory. Population of this research is all public banks existing in Indonesia in the year 1999 until 2004 which are enlisted in JSX. Purposive sampling method is used to collect data, and 120 observations are collected. Specific accrual model are used to decomposition accrual total into discretionary and nondiscretionary accrual. The existence of earnings management in banking industries is indicated by discretionary accrual not equal to zero. Banks which have not suffered health level degrade and have not violate the regulation of carefulness will do a greater earnings management by increasing balance PPAP in order to increase their assets quality. This conclusion support the research of Beaver and Engel (1986), Wahlen (1994), Moyer (1990), Niswander and Swanson (2000).